Climate Anomalies and International Migration : A Disaggregated Analysis for West Africa - Martínez Flores, Fernanda; Milusheva, Sveta; Reichert, Arndt R. (World Bank, Washington, DC, 2021)
Migration is one of the channels West African populations can use to adjust to the negative impacts of climate change. Using novel geo-referenced and high- frequency data, this study investigates the extent to which soil moisture anomalies drive international migration decisions within the region and toward Europe. The findings show that drier soil conditions decrease (rather than increase) the probability to migrate. A standard deviation decrease in soil moisture leads to a 2 percentage point drop in the probability to migrate, equivalent to a 25 percent decrease in the number of migrants. This effect is concentrated during the crop-growing season and likely driven by financial constraints. The effect is only seen for areas that are in the middle of the income distribution, with no impact on the poorest or richest areas of a country, suggesting that the former were constrained to start and the latter can address those financial constraints.